Effects of Arnica Phytotherapeutic and Homeopathic Formulations on Traumatic Injuries and Inflammatory Conditions: A Systematic Review - Claudia-Crina Toma; Mariangela Marrelli; Monica Puticiu; Filomena Conforti; Giancarlo Statti (Plants)
Arnica L. genus (Asteraceae) comprises perennial herbs native to the temperate and boreal parts of the northern hemisphere. Arnica montana is the main species. It shows different biological activities, such as antioxidant, anti-inflammatory, antibacterial, antifungal, and antitumor effects. The Arnica formulations are mainly used for pain management. This systematic review is aimed at summarizing the studies focusing on the use of Arnica products on pain and inflammatory signs due to traumatic injuries related to sport and surgical interventions as well as to arthritis and other inflammatory conditions. Both phytotherapeutic and homeopathic formulations are taken into account. This paper only includes manuscripts published in mainstream journals. A literature search from Scopus, Web of Science, and PubMed databases has been carried out using a combination of the keywords “Arnica”, “trauma”, “sport”, “injury”, “injuries”, and “pain”. According to the search strategy and inclusion criteria for this study, 42 eligible papers, focusing on both Arnica alone and formulations containing a mixture of plant extracts, have been finally selected. This review critically discusses the in vitro, in vivo, and clinical studies dealing with Arnica products, reporting both positive and negative outcomes, thus providing perspectives for future research on the plant pharmacological potential.